Statistical analysis of detected ionospheric anomalies with earthquake magnitudes: A case study of the New Zealand earthquakes of March 4, 2021 - Jewel E. Thomas; Ekong U. Nathaniel; Nyakno J. George; Aniekan M. Ekanem; Samuel S. Akpan (Results in Earth Sciences)
Statistical analysis of detected ionospheric anomalies with earthquake magnitudes was carried out on two seismic events of March 4, 2021, (M7.3 Gisborne and M8.1 Kermadec Earthquakes) to ascertain a possible link between observed perturbations and event size. GPS-TEC data were downloaded 20 days pre and 5 days post the events from stations within the epicenter of respective earthquakes. The data were statistically analyzed to detect unusual variations within the investigative window. The investigation revealed that the M7.3 Gisborne EQ shown two variations on –19 and –4 days; both being positive perturbations. However, five anomalies were detected for the M8.1 Kermadec EQ on –15, –11, –5, –3 and –2 days. With exception of the irregularities on –3 days, all others were positive anomalies. The observed anomalies were subjected to further scrutiny using the geomagnetic indices of Kernnifzer digit (kp) and disturbance storm time (Dst.) for geomagnetically induced perturbations while sunspot number and F 10.7 cm were used to monitor solar activities within this same period. The study suggested an increased in detected anomalies with earthquake magnitudes.